In Vitro and In Silico Analysis of Bergenia ciliata and Mimosa pudica for Inhibition of α-Amylase - Mahesh Bohara; Sajani Ghaju; Kabita Sharma; Surya Kant Kalauni; Karan Khadayat (Journal of Chemistry)
The discovery of antidiabetic natural products is a flourishing field of opportunity in the sector of drug discovery. Various medicinal plants with diverse chemical constituents have been extensively studied for drug development. Bergenia ciliata and Mimosa pudica have been traditionally used for the treatment of diabetes and consist of valuable phytochemicals. In this study, we have analyzed total phenolic and flavonoid content along with the antioxidant and α-amylase inhibitory activity. The crude extract of B. ciliata contains higher levels of TPC whereas higher TFC was observed in M. pudica. The strong antioxidant activity was shown by B. ciliata with an IC50 value of 125.86 ± 4.16 μg/mL. The ethyl acetate extract of B. ciliata and M. pudica showed higher α-amylase inhibitory activity with an IC50 value of 13.97 ± 0.10 and 11.97 ± 0.36 μg/mL, respectively. The biological potential of the reported phytochemicals was also assessed by using bioinformatic tools. Furthermore, the active phytochemicals from these plants were docked with human pancreatic α-amylase to study their inhibitory activities to this enzyme. The docking analysis revealed that catechin has lower binding energy (−8.6 kcal/mol) as compared to the commercial drug acarbose (−7.3 kcal/mol) indicating higher affinity towards the enzyme. This study additionally sheds more light on medicinal plants’ antidiabetic activity. So, this study will aid in the investigation of the biological properties of these plants as well as the identification of potential compounds with antidiabetic properties.